Climatic and habitat suitability of „Leontopodium alpinum” Cass. populations in the Romanian Carpathians - MAGHIAR, Lăcrămioara-Mihaela; STOICA, Ilie-Adrian (Studia Universitatis Babeș-Bolyai Biologia, 2016)
Species distribution models (SDMs) are widely used to obtain distributional knowledge in the context of incomplete biogeographic data sets. In this study we modeled the potential climatic niche of edelweiss in the Romanian Carpathians and the Alps for present and future environmental conditions. The prime objective of the study was to identify the possible impact of climate change over the distribution of this species with focus on the Carpathians. Ensemble models were fitted using the BIOMOD modeling tool in R software, for current conditions and two possible future scenarios (RCP pathways 6 and 8.5 for the year 2050). The results show that climate suitability is expected to decrease by 2050 in most of the locations considered in the study. These results outline the species sensitivity to climate warming, in agreement with previous studies.